2022
DOI: 10.1021/acs.est.2c00710
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trophic Level and Land Use on the Variation of Animal Antibiotic Resistome in the Soil Food Web

Abstract: In recent years, it has been increasingly recognized that soil animals are hidden reservoirs of antibiotic resistance genes (ARGs) and play a vital role in spreading ARGs in soil ecosystems. However, little is known about the variation of ARGs among different animals in the soil food web and effects of trophic levels and land uses on them. We characterized the antibiotic resistomes of 495 soil animal samples collected from six regions across China, including two different land uses. A total of 265 ARGs were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…These results highlight the potential for urbanization to serve as an agent of selection for the transfer of AMR into the gut of these snails and suggest that the accumulation of biological contaminants in more urban areas may increase the risk of transfer to humans. , The dominant ARGs carried by giant African snails were significantly different from those reported in soil, human gut, and other soil fauna. For instance, tetracycline resistance genes are ubiquitous and abundant in the human gut worldwide, , aminoglycoside and beta-lactam resistant genes have been shown to be the most abundant ARG types in urban park soil with reclaimed water irrigation, and multidrug resistance genes, vancomycin, and beta-lactam resistant genes are the most diverse and dominant ARGs in collembola. , However, ARGs conferring resistance to multidrug, beta-lactam, and MLS resistance genes were found to be dominant in the gut microbiome of the giant African snails we studied. Our study revealed that multidrug resistance accounted for 60% of the total ARG abundance in giant African snails, exceeding other environmental samples such as urban streams, livestock manure, and untreated urban sewage .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results highlight the potential for urbanization to serve as an agent of selection for the transfer of AMR into the gut of these snails and suggest that the accumulation of biological contaminants in more urban areas may increase the risk of transfer to humans. , The dominant ARGs carried by giant African snails were significantly different from those reported in soil, human gut, and other soil fauna. For instance, tetracycline resistance genes are ubiquitous and abundant in the human gut worldwide, , aminoglycoside and beta-lactam resistant genes have been shown to be the most abundant ARG types in urban park soil with reclaimed water irrigation, and multidrug resistance genes, vancomycin, and beta-lactam resistant genes are the most diverse and dominant ARGs in collembola. , However, ARGs conferring resistance to multidrug, beta-lactam, and MLS resistance genes were found to be dominant in the gut microbiome of the giant African snails we studied. Our study revealed that multidrug resistance accounted for 60% of the total ARG abundance in giant African snails, exceeding other environmental samples such as urban streams, livestock manure, and untreated urban sewage .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, tetracycline resistance genes are ubiquitous and abundant in the human gut worldwide, 71,72 aminoglycoside and beta-lactam resistant genes have been shown to be the most abundant ARG types in urban park soil with reclaimed water irrigation, 20 and multidrug resistance genes, vancomycin, and beta-lactam resistant genes are the most diverse and dominant ARGs in collembola. 24,73 However, ARGs conferring resistance to multidrug, beta-lactam, and MLS resistance genes were found to be dominant in the gut microbiome of the giant African snails we studied. Our study revealed that multidrug resistance accounted for 60% of the total ARG abundance in giant African snails, exceeding other environmental samples such as urban streams, 74 livestock manure, 69 and untreated urban sewage.…”
Section: Effect Of Urbanization On Giant African Snailsmentioning
confidence: 92%
“…This is because the isotopic composition of an animal’s tissue mirrors that of its prey, with a slight trophic enrichment of δ13C and δ15N of the order of 1‰ and 3.4‰, respectively [ 78 , 79 ]. δ15N is used to estimate trophic position [ 80 ], while δ13C is used to indicate relative dietary contributions from different primary sources in a food web [ 81 ]. δ13C values are typically higher (less negative) in coastal areas or benthic food webs than in pelagic food webs [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…The composition of the phyllosphere microbiome is affected by diverse factors, such as leaf age, radiation, temperature, and moisture, and these microbes are potentially mobile from the phyllosphere to soil through airflow and rain wash. Resistomes in the plant phyllosphere have a close connection with their microbiomes, , and they spread via microbial movement, forming a reservoir of resistomes in the phyllosphere with potential downstream impacts, via food chains, on animals or humans. , Therefore, it is critical to elucidate the dispersal pattern of resistomes between soil and phyllosphere and the drivers of dissemination. Multiple resistomes have been reported to be harbored in soil faunal microbiomes such as earthworms, , mites, springtails, enchytraeids, and nematodes and are shown to disperse along below-ground trophic relationships (e.g., soil–collembolan–mite and soil–nematode–earthworm), which have been enhanced by manure application. …”
Section: Introductionmentioning
confidence: 99%
“…12,20 Therefore, it is critical to elucidate the dispersal pattern of resistomes between soil and phyllosphere and the drivers of dissemination. Multiple resistomes have been reported to be harbored in soil faunal microbiomes such as earthworms, 22,23 mites, 24 springtails, 25 enchytraeids, 26 and nematodes 27 and are shown to disperse along below-ground trophic relationships (e.g., soil−collembolan−mite and soil− nematode−earthworm), which have been enhanced by manure application. 28−30 Globally, nematodes are the most abundant soil animal taxa, and it is estimated that hundreds of nematodes inhabit 1 g of soil.…”
Section: ■ Introductionmentioning
confidence: 99%